2005
DOI: 10.1353/csd.2005.0062
|View full text |Cite
|
Sign up to set email alerts
|

Body Image, Self-Esteem, and Health-Related Behaviors Among Male and Female First Year College Students

Abstract: This study examined the relationships among self-esteem, body image, and health-related behaviors of 267 female and 156 male first-year college students. Data were collected in 23 classrooms. Instruments included a demographic sheet, the Objectified Body Consciousness Scale, the Weight and Appearance Visual Analogue Scales, the Contour Drawing Rating Scale, the Rosenberg Self Esteem Scale, and a measure of physical fitness/health-related behaviors. Self-esteem was consistently related to body image dissatisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 38 publications
12
108
1
7
Order By: Relevance
“…Previous studies indicated a relationship between weight preoccupation and self esteem (e.g., Abell & Richards, 1996;Gleason et al, 2000;Lowery et al, 2005;Milligan & Pritchard, 2006;Shea & Pritchard, 2007), as well as between weight preoccupation and gender (e.g., Erol et al, 2006;Johnson et al, 2004;Macedo et al, 2007;Milligan & Pritchard, 2006;Pritchard, 2008a;Shea & Pritchard, 2007). These findings were replicated in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Previous studies indicated a relationship between weight preoccupation and self esteem (e.g., Abell & Richards, 1996;Gleason et al, 2000;Lowery et al, 2005;Milligan & Pritchard, 2006;Shea & Pritchard, 2007), as well as between weight preoccupation and gender (e.g., Erol et al, 2006;Johnson et al, 2004;Macedo et al, 2007;Milligan & Pritchard, 2006;Pritchard, 2008a;Shea & Pritchard, 2007). These findings were replicated in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…Low self-esteem has been found to relate to several types of weight preoccupation behaviors including drive for thinness (Milligan & Pritchard, 2006;Shea & Pritchard, 2007), poor body image and body dissatisfaction (Abell & Richards, 1996;Gleason, Alexander, & Somers, 2000;Lowery et al, 2005;Milligan & Pritchard, 2006;Shea & Pritchard, 2007), bulimic symptoms (Gilbert & Meyer, 2005; Mora-Giral, Raich-Escursell, Segues, Torras-Claraso, editing, corrections, structural formatting and other quality control mechanisms, may not be reflected in this document. Changes may have been made to this work since it was submitted for publication.…”
Section: Self Esteem and Weight Preoccupationmentioning
confidence: 99%
See 1 more Smart Citation
“…Better academic achievements and extracurricular activities can help in prevention of negative behaviors, better adolescents' performances, future well-being and success. [12] Several studies hint at that self-esteem impacts academic behavior. These researches propose that low self-esteem impair academic accomplishment as a result of feelings of worthlessness can be depressing and depression inhibits academic achievement.…”
Section: Introductionmentioning
confidence: 99%
“…For college students, this may be particularly challenging. Issues surrounding body image and health behaviors are a pressing concern for college students [29]. When college students feel cared for in a way that invites engagement and interpersonal support, they may be more willing and comfortable engaging in physical activity in these settings.…”
Section: Introductionmentioning
confidence: 99%